SIMULATIONS ON NICKEL TARGET PREPARATION AND SEPARATION OF Ni(II)- - Sunarhadijoso Soenarjo; Wira Rahman; Sriyono Sriyono; Triyanto Triyanto (Website, 2011)
SIMULATIONS ON NICKEL TARGET PREPARATION AND SEPARATION.OF Ni(II)-Cu(II) MATRIX FORPRODUCTION OF RADIOISOTOPE64Cu64Ni (p,n) 64 and retained on the column while the nickel was kept in the form of Ni2+ 2+ 2+ and CuCl while the nickel was totally in the form of Ni2+ while the nickel was found as both Ni2+ and NiCl while the nickel was mostly in the form of Ni2+. The retained CuCl was then changed back into Cu2+ Keywords 64 Cu, Anion exchange chromatography.: Nickel target preparation, Radioisotope Cu-64, Separation of Ni(II)-Cu(II) matrix, Nuclear reaction of 64Ni(p,n) cation form andeluted out the column by using HCl 0.05 M. The 42– 4 2–.The best condition of separation was in HCl 8 M in which the radioactive copper was mostly in the form of CuCl 42– 42– . In the condition ofHCl 9 M, the radioactive copper was mostly in the form of CuCl 42– cation. It was found that the electroplating result from the acidic solution was more satisfied than that from the basic solution. By conditioning the matrix solution at HCl 6 M, the radioactivecopper was found in the forms of Cucation and eluted off from the column. The retained radioactive copper was then eluted out the column in the condition of dilute HCl changingback the copper anion complex into Cu42– Cu. The nickel target preparation was performed by means of electroplating method using acidic solution of nickel chloride - boric acid mixture and basic solution of nickel sulphate – nickel chloridemixture on a silver- surfaced-target holder. The simulated solution of Ni(II) – Cu(II) matrix was considered as thesolution of post-proton-irradiated nickel target containing both irradiated nickel and radioactive copper, but in thepresented work the proton irradiation of nickel target was omitted, while the radioactive copper was originallyobtained from neutron irradiation of CuO target. The separation of radioactive copper from the nickel target matrixwas based on anion exchange column chromatography in which the radiocopper was conditioned to form anioncomplex CuClg-spectrometric analysis showed a single strong peak at 511 keVwhich is in accord to g-annihilation peak coming from positron decay of Cu-64, and a very weak peak at 1346 keVwhich is in accord to g-ray of Cu-64.. The simulations on Nickel target preparation and separation of Ni(II)- Cu(II) matrix has been carried out as a preliminary study for production of medical radioisotope Cu-64 based onnuclear reaction of